2020
DOI: 10.1177/0003489420946773
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Dexamethasone as a Prophylactic Treatment for Subglottic Stenosis in a Rabbit Model

Abstract: Objective: Iatrogenic injury is a common cause of subglottic stenosis (SGS). We investigated the role of pre-injury dexamethasone as a preventive treatment for iatrogenic subglottic stenosis. Methods: 16 New Zealand White rabbits were used in an IACUC approved study. Subjects were divided into two groups: intramuscular dexamethasone (DEX) at a dose of 2 mg/kg 15 minutes prior to an endoscopic injury to create SGS, and the same injury creation with a preoperative intramuscular saline (SAL) injection. Three inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A systematic review of wound‐healing agents found that SCS were poorly investigated, 162 and no relevant CPG is available. In a 2021 RCT in rabbit models, systemic administration of dexamethasone prior to induction of subglottic injury resulted in less airway stenosis 163 . The evidence on use of SCS as adjuvant treatment once stenosis is present is inconsistent.…”
Section: Laryngotracheal Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of wound‐healing agents found that SCS were poorly investigated, 162 and no relevant CPG is available. In a 2021 RCT in rabbit models, systemic administration of dexamethasone prior to induction of subglottic injury resulted in less airway stenosis 163 . The evidence on use of SCS as adjuvant treatment once stenosis is present is inconsistent.…”
Section: Laryngotracheal Stenosismentioning
confidence: 99%
“…In a 2021 RCT in rabbit models, systemic administration of dexamethasone prior to induction of subglottic injury resulted in less airway stenosis. 163 The evidence on use of SCS as adjuvant treatment once stenosis is present is inconsistent.…”
Section: Laryngotracheal Stenosismentioning
confidence: 99%
“…Endoscopic balloon dilation has proven to be a useful approach in neonates and may be successful in avoiding a tracheostomy in the neonatal period. Animal models have helped to refine the technique and have shown the value of antibiotic/steroid adjuncts [11]. At times an overlooked cause of acquired SGS, Bowles et al updated their previously published experience with subglottic cysts.…”
Section: Subglottic Stenosismentioning
confidence: 99%